Exploring the Role of Autophagy-Related Gene 5 (ATG5) Yields Important Insights Into Autophagy in Autoimmune/Autoinflammatory Diseases - Ye, Xin; Zhou, Xu-Jie; Zhang, Hong (Frontiers in Immunology, 2018)
Autophagy is a highly conserved process that degrades certain intracellular contents in both physiological and pathological conditions. Autophagy-related proteins (ATG) are key players in this pathway, among which ATG5 is indispensable in both canonical and non-canonical autophagy. Recent studies demonstrate that ATG5 modulates the immune system and crosstalks with apoptosis. However, our knowledge of the pathogenesis and regulatory mechanisms of autophagy in various immune related diseases is lacking. Thus, a deeper understanding of ATG5's role in the autophagy mechanism may shed light on the link between autophagy and the immune response, and lead to the development of new therapies for autoimmune diseases and autoinflammatory diseases. In this focused review, we discuss the latest insights into the role of ATG5 in autoimmunity. Although these studies are at a relatively early stage, ATG5 may eventually come to be regarded as a “guardian of immune integrity.” Notably, accumulating evidence indicates that other ATG genes may have similar functions.